Serotype distribution and antimicrobial susceptibility of Streptococcus pneumoniae isolates from adult patients in Jakarta, Indonesia - Wahyu F. Said; Edy Sukoto; Miftahuddin M. Khoeri; July Kumalawati; Dodi Safari (Elsevier, 2017)
Currently, the data on pneumococcal invasive disease in the Indonesian population are limited. In this study, we investigated the serotype distribution and antimicrobial susceptibility of Streptococcus pneumoniae. These samples were isolated from the sputum of adult patients with non-specific clinical symptoms aged 18-87 years in Jakarta, Indonesia, from August to October 2014. Of the 349 sputum specimens, thirteen isolates were identified as S. pneumoniae strains (4%), with two strains each for serotype 19F, 3, and 15A, and one strain each for serotype/serogroup 13, 23A, 6, 34, 17F, 16F, and untypeable. Resistance to tetracycline was most common with only 5 of 13 strains being susceptible. In conclusion, these data provide an initial in the surveillance of invasive pneumococcus in the Indonesia population. Keywords: Streptococcus pneumoniae, Sputum, Adult patient